Integration of Type Z Model with Green and Healthy Hospital Practices - Vip Paramarta; Sanny Putri Pertiwi; Brilian Segala Putra; Oktaviana Niken Prawitasari; Fransiska Camelia Subeno (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study explores the application of William Ouchi’s Type Z Model—a blend of Japanese and American management practices—within the Green and Healthy Hospital (GHH) framework at RSJD Dr. RM. Soedjarwadi, a psychiatric hospital in Indonesia. By integrating principles such as long-term orientation, participatory culture, continuous employee development, and strong leadership, the hospital improved organizational resilience and service quality while addressing environmental sustainability issues. Qualitative methods, through in-depth interviews and document analysis, were used to examine the alignment of Type Z Model principles with GHH goals, such as energy efficiency and waste management. Findings indicate that participatory decision-making fostered cohesive policies, ongoing training reduced staff turnover, and leadership supported systemic change. These collectively improved patient satisfaction and the institution’s reputation. Despite challenges such as slow decision-making, the emphasis on trust and collaboration resulted in adaptive, values-based management. This case study serves as a potential blueprint for other healthcare institutions navigating complex operational and environmental demands. Further research is recommended to examine the adaptability of this model across healthcare contexts.